2000
DOI: 10.1103/physrevlett.85.960
|View full text |Cite
|
Sign up to set email alerts
|

Topological Chern Indices in Molecular Spectra

Abstract: Topological Chern indices are related to the number of rotational states in each molecular vibrational band. Modification of the indices is associated to the appearance of "band degeneracies," and exchange of rotational states between two consecutive bands. The topological dynamical origin of these indices is demonstrated through a semiclassical approach, and their values are computed in two examples. The relation with the integer quantum Hall effect is briefly discussed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
91
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(94 citation statements)
references
References 21 publications
3
91
0
Order By: Relevance
“…In the case of rotational structure of vibrational states, classical rotational variables form a phase space which is a twodimensional sphere and the number of quantum states taken into account corresponds to a number of analyzed vibrational states counted with their degeneracies. Further studies have shown that generically the redistribution of energy levels in the rotational band structure consists in the transfer of one energy level and is associated with the modification of Chern number by one [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of rotational structure of vibrational states, classical rotational variables form a phase space which is a twodimensional sphere and the number of quantum states taken into account corresponds to a number of analyzed vibrational states counted with their degeneracies. Further studies have shown that generically the redistribution of energy levels in the rotational band structure consists in the transfer of one energy level and is associated with the modification of Chern number by one [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The relation between quantum monodromy and the phenomenon of redistribution of quantum states between branches in the energy spectrum was observed on several occasions [27,12,13] in the context of study of the same problem in pure quantum, semi-quantum, and purely classical approaches. A mathematically rigorous interpretation of such relation is still lacking.…”
Section: Discussionmentioning
confidence: 96%
“…This study is beyond the scope of the present basic RE analysis. We mention only that each band can be assigned a topological index (Chern index) [82], which gives the difference between the number of states 2J + 1 of an isolated rotational multiplet and the number of states in the band. The sum of these indexes over all components of the polyad equals zero.…”
Section: Combined Systems With Several Dynamical Integralsmentioning
confidence: 99%